The Contribution Of Brand Experience To Brand Loyalty In Beauty Products - Zenni Riana; M Endang Asmara; Amirulsyah Amirulsyah; Yusrita (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The beauty industry relies heavily on fostering consumer loyalty through trust and engaging experiences, particularly for competitive urban markets. This study aims to examine the effects of brand experience and brand trust on brand loyalty, including the moderating role of brand experience in the trust-loyalty relationship. A quantitative approach with a causal-explanatory design was employed, using a purposive sample of 308 consumers, primarily young females. Data were collected via online surveys with a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares. The findings reveal that brand trust significantly influences brand loyalty, while brand experience has no direct effect. Brand experience significantly moderates the trust-loyalty relationship negatively, suggesting that intense experiences may weaken loyalty by raising unmet expectations. In conclusion, brand trust is a key driver, but brands must carefully manage experiences to align with consumer expectations, offering insights for building sustained loyalty in Indonesia’s beauty market.